A novel heptasialosyl c-series ganglioside in embryonic chicken brain: its structure and stage-specific expression - Saito, Megumi; Kitamura, Hisayo; Sugiyama, Kiyoshi (Biochimica et biophysica acta, 2002)
A ganglioside of unknown structure (ganglioside X) was purified from chicken brain at embryonic day 12 (E12) and characterized for its structure. Ganglioside X was reactive with a monoclonal antibody A2B5 and migrated below GH1c on thin-layer chromatography (TLC). Extensive treatment of ganglioside X with Clostridium perfringens sialidase produced a single ganglioside product. This ganglioside was identified as GM1 based upon its chromatographic mobility and reactivity to cholera toxin B subunit and anti-GM1 antibody. Partial hydrolysis of ganglioside X by sialidase generated several degradation products including GH1c, GP1c, and GQ1c. Electrospray ionization (ESI)-mass spectrometry (MS) of the permethylated derivative of ganglioside X produced a triple-charged parent ion peak at m/ z 1355, which corresponded with the gangliotetraose oligosaccharide structure having seven sialic acids and ceramide with the molecular mass of 566 (as non-methylated form). Collision-induced dissociation (CID)-MS 2 showed fragment ions including those at m/ z 1066 and 1931; these two ions matched the structures of (NeuAc) 3-Gal-Glc-Cer and (NeuAc) 4-Gal-GalNAc, respectively. These structures were confirmed by CID-MS 3 of the corresponding peaks. Based upon these findings, the structure of ganglioside X was identified as NeuAc-NeuAc-NeuAc-NeuAc-Galβ1–3GalNAcβ1–4(NeuAc-NeuAc-NeuAcα2–3)Galβ1–4Glcβ1-1′Cer. This ganglioside was designated as GS1c. A developmental study demonstrated that GS1c was expressed in chicken brain during a period from E6 to E13 and thereafter decreased rapidly in its concentration. The present study suggests that GS1c may play a specific role in early development of chicken brain.